Ontario census divisions – 1966 census - Department of Mines and Technical Surveys (Producer) (Province of Ontario, 1962)
This map divides Ontario cities and towns by population density for the purpose of census divisions. A legend in the bottom left corner shows the fonts and symbols that indicate different population densities and capital cities. County boundaries are outlined, as are provincial parks and First Nations reserves. Bodies of water and geographic areas like districts are labelled. Reproduced from the 1:2,000,000 Map of Canada by the Surveys and Mapping Branch, Ottawa, 1962. Scale is 1:2,000,000. Lambert Conformal Conic Projection with Standard Parallels at 49° and 77° N Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .